Analisis Pembelajaran Ipa Pada Implementasi Kurikulum Merdeka Dalam Memenuhi Kebutuhan Pembelajaran Di Smp Negeri 1 Bua Ponrang - Umi Purnama (Qalam : Jurnal Ilmu Kependidikan, 2024)
This research aims to analyze science learning in the implementation of the independent curriculum, analyze the implementation of the science learning process, and analyze the needs of teachers and students in science learning at SMP Negeri 1 Bua Ponrang. This type of research is classified as descriptive qualitative research. The data collection techniques used were interview guides, observation sheets and documentation. The results of this research show that the science learning needs at SMP Negeri 1 Bua Ponrang have generally been met and well realized. The process of implementing science learning based on the implementation of the independent curriculum has been carried out well, implementing differentiated learning tailored to the needs of students and implementing assessments in the form of formative assessments and summative assessments. By achieving the needs in science learning, learning will be carried out well and effectively and students will be active in learning.